STUDENTS VOCABULARY MASTERY AND READING COMPREHENSION AT SMA NEGERI 1 PULAU MOROTAI - Basri, Megawati; Martora, Jasmal (Fakultas Keguruan dan Ilmu Pendidikan Universitas Pasifik Morotai, 2024)
This research examines the correlation between students’ vocabulary mastery and reading comprehension of SMA Negeri 1 Pulau Morotai. There are 94 students in class XI, quota sampling is a technique for determining a sample size; the sample is 70 students of a total number of second-grade students. The method of this research is quantitative, the researcher used 50 test questions to find students' vocabulary mastery and reading comprehension which was divided into 30 multiple-choice questions, 10 match word questions and 10 puzzle questions. All data obtained were evaluated using the Pearson Product Moment Correlation, additionally supported by the IBM SPSS Statistic SPSS 22.0 software for Windows programs. This is demonstrated by the value r-xy = 0.539 > r-table = 0.202 at a 5% significance level, which means the Moderate category, means the students who want to get high reading comprehension should have high vocabulary mastery are two inextricably linked items.